2007
DOI: 10.1210/en.2007-0605
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulation of Genes Important for K+ Channel Signaling in the Arcuate Nucleus

Abstract: Estrogen affects the electrophysiological properties of a number of hypothalamic neurons by modulating K(+) channels via rapid membrane actions and/or changes in gene expression. The interaction between these pathways (membrane vs. transcription) ultimately determines the effects of estrogen on hypothalamic functions. Using suppression subtractive hybridization, we produced a cDNA library of estrogen-regulated, brain-specific guinea pig genes, which included subunits from three prominent K+ channels (KCNQ5, Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 78 publications
6
91
0
Order By: Relevance
“…The effects of ovariectomy and estradiol treatment, however, did not differ between wild-type mice and a different strain of GPR30 Ϫ/Ϫ mice (795). A second novel ER, Gq-mER, is expressed on the cell membranes of proopiomelanocortin (POMC), dopamine, and GABA neurons in the arcuate nucleus of the hypothalamus (576,601,602). Gq-mER reduces the activation of potassium channels on GABA B and -opioid receptors and affects the expression of NPY and other neuropeptides involved in the control of energy homeostasis.…”
Section: Er Mechanisms Controlling Eatingmentioning
confidence: 99%
“…The effects of ovariectomy and estradiol treatment, however, did not differ between wild-type mice and a different strain of GPR30 Ϫ/Ϫ mice (795). A second novel ER, Gq-mER, is expressed on the cell membranes of proopiomelanocortin (POMC), dopamine, and GABA neurons in the arcuate nucleus of the hypothalamus (576,601,602). Gq-mER reduces the activation of potassium channels on GABA B and -opioid receptors and affects the expression of NPY and other neuropeptides involved in the control of energy homeostasis.…”
Section: Er Mechanisms Controlling Eatingmentioning
confidence: 99%
“…Studies are forthcoming on the cross-talk between rapid membrane-initiated and long-term nuclear-initiated steroid actions (Lagrange et al, 1994, Lagrange et al, 1997, Wagner et al, 2001b, Vasudevan et al, 2001, Kow and Pfaff, 2004, Malyala et al, 2005, Qiu et al, 2006b, Qiu et al, 2006a, Roepke et al, 2007. For example, it has been found that both acute effects of E2 and the transcriptional changes alter excitability of hypothalamic neurons , Malyala et al, 2005, Qiu et al, 2006a.…”
Section: β-Estradiol and Gnrh Neurosecretionmentioning
confidence: 99%
“…Potential targets for E 2 's rapid, nonclassical actions include membrane ERs and/or other membrane targets, which likely involve activation of several signal transduction pathways and/or second messengers, such as MAPK, extracellular signal-regulated kinase, phosphatidylinositol-3-kinase, or adenylyl cyclase cascades [27][28][29][30][31][32][33][34][35][36][37]. Indeed, we have found that co-administration of E 2 to the hippocampus with a MAPK inhibitor blocked the facilitating actions of E 2 for inhibitory avoidance performance (Figure 3).…”
Section: Rapid And/or Membrane Actions In the Hippocampus For E 2 'S mentioning
confidence: 99%